Avaliação da satisfação e qualidade de vida relacionada à saúde bucal de pacientes usuários de prótese overdenture mandibular retida por um único implante - Barcelos, Bento Alves de (2014)
The use of the single-implant mandibular overdenture has been shown as a simplified alternative for the two-implant treatment and has been presenting satisfactory results at a lower cost. The aim of this study was to evaluate patient satisfaction and oral health-related quality of life of single-implant mandibular overdenture wearers and to assess the effectiveness of different loading protocols (conventional and immediate) and two different O’ring trademarks. After delivering new conventional dentures, a single external hexagon implant was inserted in the mandibular midline region to retain an overdenture opposing to a conventional maxillary denture. Forty-five patients were treated, 38 (84.4%) achieved sufficient primary stability (final insertion torque greater than 30N and implant stability quotient greater than 60) and immediate loading was adopted and 7 (15.6%) received conventional loading since not enough primary stability was achieved. There were two implant failures in the conventional loading group and one failure in the immediate loading group, resulting in a final sample of 42 patients. A questionnaire regarding patient satisfaction in relation to the upper and lower dentures was applied and the instrument OHIP-Edent was used in order to evaluate the oral health-related quality of life. Follow-up evaluations were performed before insertion of the implant and after 3 and 6 months postoperatively. Satisfaction with the lower denture was significantly increased at the 3 months follow-up (p<0.001) and remained unchanged at the 6 months follow-up. Impact on oral health-related quality of life decreased significantly after 3 months and 6 months (p<0.001). Comparison between groups of immediate and conventional loading was infeasible because only 5 cases (11.9%) adopted conventional loading. There was no significant difference between the twoattachment trademarks regarding patient outcomes, except for the time necessary to replacement of the retention matrix, which was significantly lower in the Conexão group. It was concluded the single implant-retained mandibular overdenture treatment showed satisfactory results during the study period, suggesting that this is a feasible treatment alternative for patients with limited adaptation to the conventional mandibular denture.